The Effectiveness of the Literature Circle Method in Improving the Bahasa Rumi Writing Skills of Mattayom 3 Students at Ban Kalisa School - Nur Haida; Nikmah Sari Hasibuan; Husniah Ramadhani Pulungan; Devinna Riskiana Aritonang; Nur Afifah; Rokiyoh Maae (Institut Agama Islam Ma'arif NU (IAIMNU) Metro Lampung, 2026)
This study was motivated by the low level of Bahasa Rumi writing skills among Mattayom 3 students at Ban Kalisa School, who grow up in a linguistic environment where Thai, Malay Jawi, and Bahasa Rumi intersect. This study aims to describe the students’ initial and final abilities, as well as to analyze the effectiveness of the Literature Circle method in improving Bahasa Rumi writing skills. The study employed a quantitative approach with a quasi-experimental pretest-posttest control group design. The research sample consisted of 27 students in the experimental class and 25 students in the control class. The data were obtained through Bahasa Rumi writing tests administered before and after the treatment, then analyzed using descriptive statistics and hypothesis testing. The results showed that the mean pre-test score of the experimental class was 62.19, while that of the control class was 61.40. After the treatment, the mean post-test score of the experimental class increased to 76.93, whereas that of the control class became 68.40. The gain score of the experimental class reached 14.74, which was higher than that of the control class at 7.00. Hypothesis testing indicated significant differences in the final results and gain scores between the two classes, demonstrating that the Literature Circle method was more effective than conventional instruction. These findings highlight the pedagogical significance of structured collaborative learning in supporting the development of students’ Bahasa Rumi writing skills and suggest that the method offers a meaningful contribution to writing instruction, particularly in multilingual learning contexts